2022
DOI: 10.1039/d1tc05913k
|View full text |Cite
|
Sign up to set email alerts
|

Defining inkjet printing conditions of superconducting cuprate films through machine learning

Abstract: The design and optimization of new processing approaches for the development of rare earth cuprate (REBCO) high temperature superconductors is required to increase their cost-effective fabrication and promote market implementation....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…By optimising the available manufacturing approaches, the marketability of SCs would be enhanced. For this purpose, the ML-based method was used in [242] to produce REBCO tapes with higher level of marketability and lower cost. The data were acquired by drop-on-demand inkjet printing of the REBCO precursor.…”
Section: Ai Techniques For Magnetic Levitationmentioning
confidence: 99%
“…By optimising the available manufacturing approaches, the marketability of SCs would be enhanced. For this purpose, the ML-based method was used in [242] to produce REBCO tapes with higher level of marketability and lower cost. The data were acquired by drop-on-demand inkjet printing of the REBCO precursor.…”
Section: Ai Techniques For Magnetic Levitationmentioning
confidence: 99%
“…It is not a trivial goal then to control all the relevant parameters involved in solution deposition by IJP because it is needed to adapt the solutions to the sort of nozzles to be used. For instance, a recent use of machine learning analysis of fluorine-free IJP solution deposition has shown that high throughput experimentation may help to predict the most relevant processing parameters (drop volume, drop pitch, wettability, solvent evaporation rate, etc) [143,147].…”
Section: Solution Deposition and Pyrolysis Analysismentioning
confidence: 99%
“…Understanding the main trends of REBCO nucleation and growth has strongly facilitated to prepare CCs using different metallic substrates (RABiT, IBAD) leading to fairly good superconducting performances, including the reel-to-reel continuous process used at industrial scale [30,58,140,142,[169][170][171][172]. It is also worth to remark that owing to the global complexity of the CSD BaF 2 growth process, several attempts of using experimental fast screening and big data approaches have been made to accelerate the optimization of CCs and to correlate processing, nanostructure and superconducting properties [143,147,173].…”
Section: Nucleation Growth and Oxygenation Of Pristine Rebco Films An...mentioning
confidence: 99%
“…Recently, we demonstrated that using fluorine-free solutions in a kinetically driven CSD approach, fabrication of YBCO layers could be attained at growth rates beyond 100 nm/s. This method, known as transient liquid-assisted growth (TLAG) process, promotes a cost-effective, high-throughput, and scalable growth of CC manufacturing, which can also benefit from combinatorial approaches to accelerate the experimentation and development of films with high performance. The novelty of TLAG lies in the fact that it employs a two-step nucleation mechanism in non-equilibrium conditions, starting from the formation of a transient liquid of Ba–Cu–O in which solid Y 2 O 3 nanoparticles are dispersed, which occurs in a region of the phase diagram in which, instead, solid phases (like YBCO) are energetically favored. The Y 2 O 3 dissolution in the transient liquid and the high atomic mobility of Y in the liquid favor Y diffusion toward the nucleation front of YBCO nuclei and, thus, its ultrafast epitaxial growth through a liquid–solid reaction. ,, The driving force of this process is the Y supersaturation in the transient liquid, a parameter strongly controlled by the composition of the latter and easily modified through the stoichiometry of the precursor solutions.…”
Section: Introductionmentioning
confidence: 99%